Study of Anti-hyperuricemia, Anti-inflammatory, and Anti-nociceptive Effects of Hylocereus undatus Stem Bark Extract in Animal Models - Tri Wahyuni; Sartika Harka Putri; Anton Bahtiar (Universitas Indonesia, 2023)
Dragon fruit, known as Hylocereus undantus (HU), has traditionally been utilized in Banyuwangi, East Java, Indonesia, for addressing gout and rheumatism. Despite its empirical use, there is a lack of reported pharmacological research on this plant. This study aimed to explore the properties of HU extract in treating hyperuricemia, inflammation, and pain. Adenine-potassium oxonate-induced mice were employed to evaluate anti-hyperuricemia activity, measuring uric acid, blood urea nitrogen (BUN), and creatinine serum levels. Carrageenan-induced paw edema in rats was used to assess anti-inflammatory activity, while acetic acid-induced abdominal writhing and hot plate tests were conducted to investigate anti-nociceptive effects. The results revealed that administering HU extracts at 400 mg/kg notably reduced uric acid levels (p<0.01). Moreover, doses of 100, 200, and 400 mg/kg showed significant reductions in BUN and creatinine serum levels (p<0.0001). At a dose of 400 mg/kg, HU extract exhibited a significant anti-inflammatory effect two hours post-administration, manifesting a 15% and 26% reduction in paw edema for male and female mice, respectively (p<0.005, p<0.001). Additionally, doses of 200 and 400 mg/kg demonstrated anti-nociceptive effects in acetic acid-induced abdominal constriction. Furthermore, at 400 mg/kg, the extract exhibited anti-nociceptive activity (p<0.001) three hours post-administration using the hot plate method. This study underscores the potent anti-hyperuricemia, anti-inflammatory, and anti-nociceptive properties of HU. The implications of these findings contribute significantly to comprehending the therapeutic potential of HU.